Implementation and evaluation of a store-and-forward teledermatology workflow in a United States safety-net hospital urgent care emergency center: A retrospective cohort studyCapsule Summary - Christian L. Carr, MD; Aya Alame, MD; Benjamin F. Chong, MD; Melissa Mauskar, MD; Jeffery Metzger, MD; Catherine Neal, MD; Joan S. Reisch, PhD; Arturo R. Dominguez, MD (Elsevier, 2023)
Background: Teledermatology (TD) is an important method for increasing access to care in outpatient settings. However, less is known regarding its use in emergency/urgent care centers. Objective: To evaluate the effect of TD on urgent care emergency center (UCEC) dwell time and postencounter utilization. Study type and methods: This retrospective cohort study evaluated patients in a safety-net hospital (Parkland Health, Dallas, Texas, USA) UCEC, who (1) received a TD consult in 2018, (2) were referred to dermatology clinic in 2017, or (3) were referred to dermatology clinic in 2018 without a TD consult. Results: We evaluated 2024 patients from 2017 to 2018. Of the 973 referred to dermatology clinic in 2018, 332 (34%) received TD consultations. Mean dwell time for patients receiving TD was longer versus the 2017 cohort (303 vs 204 minutes, respectively). Patients receiving TD consultation with inflammatory skin conditions had lower odds of dermatology clinic visits compared with those that did not (odds ratio, 0.5; 95% CI, 0.3-0.8). Teledermatology was not associated with differences in repeat UCEC utilization. Limitations: Single institution study and inability to account for differences in patient complexity. Conclusion: TD increases dwell time in a safety-net hospital's UCEC but can reduce dermatology clinic utilization for patients with inflammatory skin conditions.